Secure by Design: Proactive Approaches to Embedded System Security - Dr. N. Kala; Premanand Narasimhan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
As embedded systems proliferate across industries such as healthcare, automotive, and consumer electronics, ensuring their security has become a critical imperative. The increasing complexity and connectivity of these systems expose them to a myriad of cyber and physical threats, necessitating robust strategies for risk mitigation. This paper explores the need for enhanced security in embedded systems, addressing challenges such as striking a balance between business requirements and security, managing growing connectivity, and ensuring cybersecurity and information assurance. A detailed classification of threats, including physical, network-based, software, and insider attacks, is provided to underscore the scope of potential vulnerabilities. The paper outlines practical guidelines for improving security, emphasizing end-to-end threat assessments, leveraging advanced designs, and adopting comprehensive life cycle support. Furthermore, it presents practical design solutions spanning enclosures, circuit boards, and firmware to safeguard against emerging threats. By adopting these strategies and solutions, embedded systems can achieve heightened resilience and operational reliability, ensuring trust in critical applications.